Highly sensitive SERS sensor for mercury ions based on the catalytic reaction of mercury ion decorated Ag nanoparticles1. Issue 61 (4th July 2015) - Qi, Guohua; Fu, Cuicui; Chen, Gang; Xu, Shuping; Xu, Weiqing
<x xml:space="preserve">Abstract</x> Schematic diagram of the SERS sensing mechanism for mercury ions by a catalytic oxidation reaction.